Knowledge Science, Engineering and Management 5th International Conference, KSEM 2011, Irvine, CA, USA, December 12-14, 2011. Proceedings - Xiong, Hui.; Lee, W. B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 5th International Conference on Knowledge Science, Engineering and Management, KSEM 2011, held in Irvine, CA, USA, in December 2011. The 34 revised full papers presented together with 7 short papers were carefully reviewed and selected from numerous submissions.
Keywords: Computer science; Information systems; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Data Mining and Knowledge Discovery; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Information Systems and Communication Service